Research Advances on the Rotational Doppler Effect of Vortex Electromagnetic Waves - Zhongyi GUO; Yanzhe WANG; Yunlai WANG; Kai GUO (Leida xuebao, 2021)
Traditional radars can detect moving targets using the Doppler effect. However, traditional radars have shadow areas in detecting the angular motion of the rotating targets. The discovery of the rotational Doppler effect based on vortex electromagnetic waves helps solve the problem of detecting the angular motion of the rotating targets under direct vision, which has attracted considerable attention from domestic and foreign scholars. In this study, we discussed the recent research progress on the rotational Doppler effect of vortex electromagnetic waves, particularly for related results in the microwave band, including the rotational Doppler effects on the target under on-axis and off-axis cases; decoupling linear Doppler, micro-Doppler and rotational Doppler effects under complex motion cases; and rotational Doppler effects on the applications of radar imaging and velocity measurement. We summarized and analyzed the existing problems demanding prompt solutions in this field, and proposed future research directions and relative applications.